INTEGRATED IOT- BASED WATER QUALITY SYSTEM USING FOUR PARAMETERS FOR SUSTAINABLE WATER RESOURCE MANAGEMENT - Makin, N. A.; Azahari, A. H.; Firdaus, A. Z. M.; Mohamad, H.; Abdulrahim, K.; Rahman, S. A.; Ismail, W. Z. W.; Jamaludin, J.; Othman, M.; AzizulRahman, N. A.; Anuar, N. H. Z.; Seman, K.; et al. (Journal of Engineering and Technology (JET), 2026)
In Malaysia, the degradation of water bodies due to rapid urbanisation, agricultural runoff, and industrial waste highlight the urgent need for continuous, efficient water quality monitoring. However, current manual-based sampling methods are time-consuming, labour-intensive, and insufficient for real-time assessment, thus limiting proactive intervention. In response to these limitations, this study aims to design an integrated water quality monitoring system that focuses on four parameters which are Dissolved Oxygen (DO), pH, Temperature, and Turbidity. These parameters selected for their importance in assessing aquatic health and pollution levels. To achieve this, the system design incorporates Arduino as the central microcontroller for sensor integration, coupled with Long Range (LoRa) communication for energy-efficient, long- range data transmission. Sensor data are envisioned to be transmitted to a cloud- based dashboard for real-time monitoring and analysis. The proposed design is expected to lay the groundwork for a scalable and cost-effective solution that enhances monitoring accessibility, reduces reliance on manual sampling, and supports proactive water resource management aligned with Sustainable Development Goal (SDG) 6: Clean Water and Sanitation.